INFRARED THERAPY FOR CLIENTS WITH DIABETIC GANGRENE AT THE SURABAYA WOUND CARE HOME : ANALITYCAL DESCRIPTIVE STUDY - Sumiyati, Sumiyati; Hidayat, Arifin (Lux Mensana: Journal of Scientific Health, 2024)
Introduction : Diabetic gangrene is a complication of Diabetes Mellitus due to chronicneuropathy, vascular insufficiency and infection. Aggressive therapy for diabetic gangrene isneeded so that leg amputation can be avoided, one of which is treating local wounds in the legarea using the infrared method. Research. Method: Descriptive analytic with a cross sectionalapproach was used in this research. The research respondents were 30 patients whounderwent infrared treatment at the Surabaya Wound Care Home in Sidoarjo. The aim of thisstudy was to determine the factors that influence compliance with infrared therapy. Result &Analysis : The research results showed that 18 respondents (60%) complied and 12respondents (40%) did not comply, mean: 35.36 and standard deviation: 4.94. Discussion :Respondents who did not comply with infrared therapy were influenced by: the perceivedbenefits of the wound healing process were not felt enough, the length of the wound healingprocess, feelings of laziness caused respondents not to comply with recommendations,wounds that improved caused respondents to stop therapy.